A Comparative Clinical Study to Evaluate the Effect of Jatamansi churna and nirgundi taila padabhyanga in Nidranasha - Pradhan, Manasi; Sahoo, Manoj Kumar; Nayak, Simadri Bhusan (International Research Journal of Ayurveda & Yoga, 2024)
Background: According to Ayurveda, there are three pillars of life such as Ahara, Nidra, and Brahmacharya and among them, Ayurveda gives more importance to Nidra (sleep). Sleep is an essential phenomenon for the maintenance and restoration of both body and mind, and thus, Nidra is a precious gift by nature, which is directly connected with the mental state. Keeping in view the importance of sleep, the present work aimed at comparing the efficacy of Jatamansi churna versus Nirgundi taila padabhyanga with respect to Nidranasha. Materials and Methods: 40 numbers of patients were taken for the study and all patients were divided into two equal groups, i.e., Group A and Group B. Group A consisted of 20 patients were treated with Jatamansi Churna internally for 15 days. Group B consisted of 20 patients were treated with Jatamansi Churna internally and Nirgundi taila Padabhyanga for 15 days. A comparison was done between Group A and Group B and the assessment was made before and after treatment. Results: The better result was obtained in Group B in reducing the subjective and objective parameters of Nidranasha than Group A. Conclusion: It can be said that, internal application of it can be said that, internal application of Jatamansi Churna along with Nirgundi Tila Padabhyanga could be the effective tools for the management of Nidranasha along with Nirgundi Tila Padabhyanga could be the effective tools for management of Nidranasha.